INVESTIGATION INTO ATHEISM OF RHAZES (ABU BAKR AL-RAZI) - Dr Bushra; Ms Tahira Akber; Ms. Hajrah; Nazia wali Muhammad; MS Rabia Mushtaq; Anisa (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Abu Bakr Muhammad bin Zakariyya al-Razi, known in the West as Rhazes, was great Muslim Scientist especially a medical expert, philosopher, and a polymath of the 10th Century CE. His works have been translated into many languages of the world and his books have been taught until seventeenth century in the Europe. However, some European scholars have claimed that al-Razi was an atheist who neither believes in the divine institution of the Prophecy nor believes in the religious scriptures. This paper deals with this important issue to reach a conclusion. For this, the concerned literature has been carefully studied to reach the conclusion. In this regard, the concerned book of al-Razi has also been studied. After the careful study and mindful investigation into the literature, this paper argues that the claim of atheism has not been substantiated with strong and unequivocal arguments. The books on which this claim has been made are not extant and not included in the list of the works of al-Razi.